Treasure From The Colonial Past: The Reading Of Sir Frank Swettenham's Short Stories 'A Silhouette' and'A Mezzotint'. - Pakri, Dr. Mohamad Rashidi (2006)
The conquest of the earth, which mostly means the taking it away from those who have a different complexion or slightly flatter noses than ourselves, is not a pretty thing when you look into it too much.